Graphene oxide prevents lateral amygdala dysfunctional synaptic plasticity and reverts long lasting anxiety behavior in rats. (April 2021) - Franceschi Biagioni, Audrey; Cellot, Giada; Pati, Elisa; Lozano, Neus; Ballesteros, Belén; Casani, Raffaele; Coimbra, Norberto Cysne; Kostarelos, Kostas; Ballerini, Laura
Abstract: Engineered small graphene oxide (s-GO) sheets were previously shown to reversibly down-regulate glutamatergic synapses in the hippocampus of juvenile rats, disclosing an unexpected translational potential of these nanomaterials to target selective synapses in vivo . Synapses are anatomical specializations acting in the Central Nervous System (CNS) as functional interfaces among neurons. Dynamic changes in synaptic function, named synaptic plasticity, are crucial to learning and memory. More recently, pathological mechanisms involving dysfunctional synaptic plasticity were implicated in several brain diseases, from dementia to anxiety disorders. Hyper-excitability of glutamatergic neurons in the lateral nucleus of the amygdala complex (LA) is substantially involved in the storage of aversive memory induced by stressful events enabling post-traumatic stress disorder (PTSD). Here we translated in PTSD animal model the ability of s-GO, when stereotaxically administered to hamper LA glutamatergic transmission and to prevent the behavioral response featured in long-term aversive memory. We propose that s-GO, by interference with glutamatergic plasticity, impair LA-dependent memory retrieval related to PTSD.